Business Development Strategy of Salt Diversification Product in Cirebon Regency - Sugiarto, Sugiarto; Mudzakir, Abdul Kohar; Suryanti, Suryanti (Budapest International Research and Critics University, 2021)
CV Rama Shinta as a producer of salts diversified products for beauty and health requires a business development strategy design to increase the company so that it can contribute larger to solve the problem of salt prices faced by the coastal community. The purpose of this study was to (1) determine the recommendation of business development strategy for salt product diversification at CV Rama Shinta, (2) determine the priority business development strategy for salt product diversification at CV Rama Shinta, and (3) determine the implementation method of the product diversification business development strategy at CV Rama Shinta with strategic architecture. The method used in this research is identifying internal and external factors of the company to formulate strategic recommendations using IFE and EFE matrix analysis, IE matrix, SWOT matrix, QSPM and strategic architecture. The result of SWOT matrix and QSPM analysis showed that there’s 12 strategics recommendations with strategic priorities are to maximizing promotions activities. The strategic architecture mapping recommends three stages of implementation, which is the short term, medium term, and long-term strategic implementation.